(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article explores the important interaction between political modernization and civil society and its impact on the democratic process. Political modernization, as a key component of modern political development, includes changes in institutions, structures and processes, as well as in behavioral norms and values in the political system. Civil society, in turn, plays the role of an active participant and controller of political processes, contributing to the creation of transparent, responsible and sustainable democratic institutions. The article examines how these two phenomena interact, in particular, how civil society can influence the process of political modernization through active civic engagement, monitoring political reforms and advocating for the observance of citizens’ rights and freedoms. Conversely, political modernization can help strengthen civil society by creating legislative and institutional mechanisms that promote civic engagement and participation.